A new stage of kazakhstan's migration policy (Journal of Philosophy Culture and Political Science, 2024)
The problem of migration in the country is one of the most relevant topics today. The policy of resettlement from a densely populated region to the north is particularly lame. According to official data, about two hundred thousand people have immigrated to our country since 2012, and on the contrary-almost four hundred thousand people, that is, twice as many.The imbalance in the location of the population by region in the Republic of Kazakhstan, according to which different economic development between regions, the emergence of the need for the redistribution of labor – labor resources – have changed attitudes towards migration policy, increased concerns about the regulation of internal migration. As a sparsely populated state with a large territory, but populated there, it is obvious that in recent years there has been a large disparity in the settlement of the population throughout Kazakhstan.As one of the measures to restore this imbalance, a state program of voluntary placement of the population from the southern regions to the northern regions has been implemented. Some conditions have been created for those who have moved to the north, there are various benefits and financial incentives.To put an end to such interregional inequality, the government of the country first approved the state program "Enbek" and within 5 years tried to move the South to the north. Although this program did not produce the expected results, it contributed to the intensification of internal migration in the right direction, distinguishing the pros and cons of internal migration.In 2022, a new national project "strong regions – the driver of the country's development" was launched. After the shortcomings of the previous program were revealed, new opportunities and new benefits will now be provided to the settlers. The authors of the article analyze these initiatives of the state and dwell on the events that became the prerequisites for the emergence of such an interregional disparity. In addition, it will analyze what other measures should be taken to improve migration policy and propose a number of solutions.Keywords: demography, migration processes, population size, national interests, disproportion, "Migration policy concept", labor exchange, internal migration.